Identification of building repair policy choice criteria role - Dytczak, Mirosław; Ginda, Grzegorz (Technological and Economic Development of Economy, 2009)
Preparation of building repair activities in multi‐family dwelling houses poses an important problem for habitat co‐operatives in Poland. Firstly, such co‐operatives own and manage a lot of buildings. Secondly, scarcity of economic and non‐economic resources requires their effective allocation. Such allocation should be based on properly prioritised actions’ alternatives. Unfortunately, due to the complex influence of the surrounding environment, the influence of a considerable number of components and diverse point of views is to be included during the analysis of repair needs. Potential influences result from a bunch of sources. The sources are of economic, technological, social and environmental nature. To support a decision‐maker effectively, information pertaining to the importance of particular influences is required. Such information can be obtained by special means of multi‐criteria decision analysis (MCDA) methodology. The application of the chosen approach – Decision Making Trial and Evaluation Laboratory (DEMATEL) for classification of repair needs assessment criteria to shape repair policy appropriately is presented in this paper.Pastatų remonto strategijos parinkimasSantrauka. Pasirengimas remontuoti daugiabučius gyvenamuosius namus sukelia daug problemų tokių namų kooperatyvams Lenkijoje. Pirma, tokie kooperatyvai turi ir valdo daug pastatų. Antra, dėl nepakankamų ekonominių ir neekonominių išteklių reikia juos efektyviai paskirstyti. Toks paskirstymas turi būti pagrįstas išnagrinėjus alternatyvas ir nustačius prioritetines. Deja, remonto poreikio analizę veikia sudėtinga aplinka. Tam įtaką daro daug komponentų, reikia suderinti įvairius požiūrius. Potenciali įtaka kyla iš šaltinių gausos. Yra ekonominiai, technologiniai, socialiniai ir gamtinės aplinkos šaltiniai. Efektyviam sprendimui priimti reikia turėti informacijos apie įtakos svarbą. Tokiai informacijai gauti gali būti pritaikyta speciali daugiakriterinės sprendimų analizės metodologija. Straipsnyje pristatomas metodas, kuriuo vertinami remonto poreikio kriterijai ir padedama suformuluoti remonto politiką.Reikšminiai žodžiai: statybos inžinerija, gyvenamųjų namų kooperatyvas, daugiabutis namas, remontas, poreikiai, klasifikacija, dalyviai, daugiakriterinis vertinimas, jautrumo analizė.First published online: 21 Oct 2010